Sen kategoriasta - onko suomessa jo artikkeli? - Laury, Ritva (Virittäjä, 1996)
Regarding the category of se: does Finnish have an article yet? (englanti) 2/1996 (100) Ritva Laury (Department of Linguistics, California State University, Fresno; edu) REGARDING THE CATEGORY OF SE: DOES FINNISH HAVE AN ARTICLE YET? This paper concerns the current lexical category of the determiner se in spoken Finnish. Although linguists have known at least since the late 1800s that the demonstrative se is developing into a definite article, there has been a lack of general agreement about the contexts in which se may or may not be used. However, those who have researched this topic do generally agree that se is not yet an article. This paper takes the opposite view. Based on an examination of the use of se in a database consisting of spoken narratives and ordinary conversations, the author proposes that se is already an article. Viewed from the perspective of Greenberg’s (1978) diachronic typology, the Finnish se is no longer a Stage 0 demonstrative on its way to becoming an article. In that stage of the development, according to Greenberg, the future article is typically used to refer back to something that has already been mentioned earlier. While se was most commonly used in such contexts in narratives recorded in the late 1800s, in more recently recorded narratives, se is used as a general marker of identifiability, regardless of earlier mention, which would make it a Stage I article in Greenberg’s typology. In the most recent data recorded in the 1970s, 80s and 90s, se is also used more frequently than what would be expected of a demonstrative, and its use frequency approaches that of articles in those languages that have them, particularly so for younger speakers. Further, se is omitted in contexts which resemble those in which languages that do have articles also use bare NPs. Se is not used with proper names, kinterms, and NPs referring to other situationally bound social roles when they are used as co-recognitionals (Downing 1995); it is also left out with NPs which are not used discourse referentially (Du Bois 1980), such as body part nouns and certain types of obliques. The author suggests that while se is already an article in spoken Finnish, it is not yet fully grammaticized, but that the contexts in which se is used and those in which it is left out display rather transparently the motivations which have lead to the grammaticization of definite articles in certain contexts in article-bearing languages.